A LESSON DESIGN OF ALGEBRAIC THINKING IN ELEMENTARY SCHOOL AS AN EFFORTS TO DEVELOP MATHEMATICAL LITERATION IN INDUSTRIAL ERA 4.0 - Vira Pratiwi; Laely Farokhah; Zaenal Abidin (IKIP Siliwangi, 2019)
Algebraic thinking is one of the abilities needed in the industrial era 4.0. The efforts to instill algebraic thinking need to be done since elementary school students. Before students learn about algebra, they must have a lot of experience in making representations, abstractions, and generalizations. The ability to represent data using tables and diagrams is one indicator of algebraic thinking. This research was conducted discovery of learning obstacles thinking algebra by representing data using tables and diagrams in elementary school. Learning obstacles include ontogenically obstacles, epistemological obstacles, and didactical obstacles. Therefore, it is necessary to develop didactic designs to overcome these learning obstacles. The research method used was Didactical Design Research (DDR). This research was conducted by analyzing learning obstacles that were found to be used as the development of learning trajectories. The analysis process produces alternative didactic situations that can overcome obstacles in thinking algebra. Given that algebraic thinking in the curriculum in elementary schools is still implied, it is necessary to develop a comprehensive lesson design to facilitate students in developing algebraic thinking. The ability to think algebra is the high order thinking skills, they need to face various challenges today.